'You're a woman, a convenience, a cat, a poof, a thing, an idiot': Transgender women negotiating sexual experiences in men's prisons in Australia. (March 2017) - Wilson, Mandy; Simpson, Paul L; Butler, Tony G; Richters, Juliet; Yap, Lorraine; Donovan, Basil
We examine the lived experiences of transgender women in Australian men's and women's prisons. We draw on Alice Ristroph's sexual punishments framework to discuss the diversity and ambiguities of sexual experiences reported by participants, and argue for a need to move beyond the dominant narrative of prison rape.